2009
DOI: 10.1002/pola.23699
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of crosslinked microspheres and porous solids from hydrocarbon solutions: A new variation of precipitation polymerization chemistry

Abstract: A new variation of precipitation polymerization is described wherein CH bond addition to a triallyl monomer contributes to molecular weight growth, thereby incorporating a significant amount of saturated hydrocarbon into the solid phase. The extent of monomer oligomerization relative to hydrocarbon addition is shown to increase with the concentration of allyl benzoate in cyclooctane. An extension to the trifunctional monomer, triallyl trimesate, results in phase separation of hydrocarbon‐monomer adducts to gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In general, reaction with coagents bearing multiple acrylate, allylic or styrenic groups results in bimodal molecular weight and branched distribution, comprised of a linear chain population of relatively low molecular weight, and a high molecular weight hyper‐branched chain population, which can progress above the gel point . Furthermore it has been reported that systems containing polypropylene reacted with coagent and peroxide can undergo a precipitation polymerization, which results in the formation of a separate phase of highly cross‐linked, coagent‐rich sub‐micron sized particles . The resulting products possess a creamy appearance in the melt state, owing to the presence of these cross‐linked nano‐particles …”
Section: Resultsmentioning
confidence: 99%
“…In general, reaction with coagents bearing multiple acrylate, allylic or styrenic groups results in bimodal molecular weight and branched distribution, comprised of a linear chain population of relatively low molecular weight, and a high molecular weight hyper‐branched chain population, which can progress above the gel point . Furthermore it has been reported that systems containing polypropylene reacted with coagent and peroxide can undergo a precipitation polymerization, which results in the formation of a separate phase of highly cross‐linked, coagent‐rich sub‐micron sized particles . The resulting products possess a creamy appearance in the melt state, owing to the presence of these cross‐linked nano‐particles …”
Section: Resultsmentioning
confidence: 99%
“…The molar masses and zero shear viscosities of the CM-PPs were lower than those of the starting L-PP (Tables 1 and 2) suggesting that chain scission was the dominant reaction in both coagent modifications. Radical addition and hydrogen transfer reactions involving a coagent decrease the population of PP macroradicals, thereby suppressing β -scission of tertiary alkyl radical intermediates, 26 thus resulting in higher molar masses and viscosities compared to the formulations treated with the same amount of DCP (Tables 1 and 2). The molar masses of most CM-PPs were comparable to DCP-PP treated with 0.1 DCP, therefore this formulation is used as a basis for comparison in the following discussion.…”
Section: Resultsmentioning
confidence: 99%
“…11 The formation of these nanoparticles is likely attributed to a precipitation polymerization mechanism, wherein acrylate coagent oligomerization yields adducts that are insoluble in the polymer melt, leading to the separation of a coagent-rich phase that cross-links to a very high extent. 26 Given their yield, between 1 and 3 wt% in PP-g-TMPTMA, these particles may be responsible for the presence of the significant secondary relaxation observed in this material. 31,32 We have shown that these particles result in a substantial nucleation phenomenon during crystallization and significant shifts in the crystallization temperature.…”
Section: Cm-pp Characterization and Foamingmentioning
confidence: 93%
“…The current work is concerned with the relationship between the structure of a macromonomer's functionality and the material's crosslinking dynamics and yields. Scheme illustrates the macromonomers of interest, which range from highly reactive acrylates and styrenics, to relatively unreactive maleate diesters and unactivated allylic monomers . Some of these functional groups have been studied extensively in the context of low temperature homopolymerization, with reliable estimates of the propagation rate constants providing insight into the potential reactivity of a given macromonomer system.…”
Section: Introductionmentioning
confidence: 99%